Promotion and Marketing System using Social Media at UMKM Omer Prata & Teh Tarek - Muhammad Donal Mon; Violina Anastasya (Universitas Internasional Batam, 2023)
This study aims to implement promotional and marketing strategies using social media for UMKM Omer Prata & Teh Tarek through social media, namely Instagram by creating attractive promotional content and creating accounts on the online ordering application, namely Go-Food. The implementation aims to provide solutions to increase sales and revenue, reach more new customers and make it easier for customers to place orders online. Data collection in this study used 3 techniques namely observation, interviews, and documentation. The results obtained are that Omer Prata & Teh Tarek are better known by new potential customers and get an increase in orders and revenue. This can be a recommendation for further research in order to increase the creation of interesting content on social media for promotion and marketing strategies in terms of increasing sales and revenue.